Phenolic profiles and antioxidant activities of free, esterified and bound phenolic compounds in walnut kernel. (15th July 2021) - Wu, Shutian; Shen, Danyu; Wang, Ruohui; Li, Qingyang; Mo, Runhong; Zheng, Yuewen; Zhou, Ye; Liu, Yihua
Highlights: The majority phenolics in walnut kernel were free phenolics. Acetone was better to extract soluble phenolics, and methanol for insoluble bound phenolics. Jeuglone, kaempferol, quercetin-7-o-β-D -glucoside and dihydroquercetin were only found in free phenolics. There was positive linear correlation between antioxidant activities and total phenolic contents. Abstract: The free, esterified and bound forms of 37 phenolic compounds (including hydroxybenzoic acid, hydroxycinnamic acids, flavanols, flavonols and flavones) from walnut kernel ( Juglans regia L.) were investigated in this study. Results showed that the majority of walnut phenolics were presented in the free form (51.1%–68.1%), followed by bound (21.0%–38.0%) and esterified forms (9.7%–18.7%). Ellagic acid, gallic acid, ferulic acid, sinapic acid and caffeic acid were widely distributed in three forms. Differently, jeuglone, kaempferol, quercetin-7-o-β-d -glucoside and dihydroquercetin were only found in free phenolics. Among the three forms, free phenolics had the highest radical scavenging activity (IC50 : DPPH, 15.5 µg/ml; ABTS, 13.6 µg/ml). The correlation coefficients between the antioxidant activities of phenolics and their corresponding contents were 0.82–0.92. More soluble phenolics (free and esterified forms) could be extracted by acetone, while methanol was better at extracting insoluble bound phenolics.